THE NEED FOR MUSIC EDUCATION IN THE 21ST CENTURY - Raximova Mavluda Nabijonovna (Galaxy International Interdisciplinary Research Journal, 2021)
Children of all walks of life received emotional education through musical culture. In everyday life, the child heard his mother's lullabies, folk music, among which he grew up. All folk holidays and ceremonies were accompanied by singing, dancing, and the sound of folk instruments. At divine services in the church, a person joined the high world of sacred music, which raised him morally, educated and educated. Music helped the child to learn about the whole world, formed the intellectual, volitional and moral qualities of a person, awakened and stimulated his creative powers and abilities.